Analisis Penerapan Model Problem Based Learning (PBL) dalam Meningkatkan Keaktifan dan Kemampuan Pemecahan Masalah pada Pembelajaran IPS Siswa Kelas VI Sekolah Dasar - Nayla Chariza; Mulia Sri Huljanah; Nelsi Gusni; Novita Vellya Sari; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low level of student activeness and problem-solving ability in Social Studies (IPS) learning remains a challenge that requires innovative learning approaches. This study aims to analyze the implementation of the Problem Based Learning (PBL) model in IPS learning for sixth-grade students at SDN 31 Selayo and examine its influence on student activeness and problem-solving ability from the teacher’s perspective. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with the sixth-grade homeroom teacher, supported by document analysis and literature review. The findings indicate that prior to implementing PBL, the learning process was teacher-centered, resulting in low student participation, where students rarely asked questions, hesitated to express opinions, and struggled to connect lesson content to real-life situations. Following the implementation of PBL, noticeable improvements were observed, as students became more active in asking questions, expressing ideas, participating in discussions, and presenting solutions collaboratively, while also demonstrating increased confidence in communication and argumentation. In terms of problem-solving ability, students showed progress in identifying problems, collecting relevant information, generating alternative solutions, and evaluating solutions critically before making conclusions. Although several challenges emerged during implementation, including students’ unfamiliarity with independent learning, time management issues, and increased classroom complexity, these obstacles were gradually addressed through adaptive teaching strategies. The findings suggest that PBL effectively creates a more interactive, collaborative, and critical learning environment, thereby improving student activeness and problem-solving ability in elementary Social Studies learning.